Relasi Kuasa Dalam Akreditasi Perpustakaan Perguruan Tinggi - Unyil, Unyil; Sri Rohyanti Zulaikha, Sri Rohyanti Zulaikha (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to describe the power relations of Michel Foucault in the accreditation of higher education libraries in Indonesia. Given the large role of the higher education library in supporting the implementation of education in the tertiary institution itself, accreditation as a formal recognition of quality assurance or the fulfillment of quality standards in implementation needs to be questioned. The data proves that from 2,057 university libraries in Indonesia, 722 have just been accredited, so the researchers tried to conduct a study by looking at Foucault's power relations in accrediting university libraries. The method used in this research is exploratory descriptive method. The results of this study convey that the accreditation of higher education libraries has Foucault's theory of power relations. This can have an impact on the organizational structure of the library manager in implementing and managing the library. The organizers and managers in question are the implementation and management as mandated by Law no. 43 of 2007 and PP no. 24 of 2014 and SNP no. 13 of 2017 which meets library standards, but it needs to be understood that Foucault's theory of power relations only gives to anyone freely, whether it's the power of one's own will or power over one's position and whether the effect is good or bad depends on the person who uses that power himself.